Conservative treatment for fractures of the scaphoid - Chang, Nick; Grewal, Ruby (Handchirurgie · Mikrochirurgie · Plastische Chirurgie, 2020)
This review article aims to discuss the indications, techniques, outcomes, and complications of non-operative management of scaphoid fractures.
Keywords: Scaphoid fracture; conservative treatment; non-operative treatment